Ammonia gas adsorption on metal oxide nanoparticles - Mohammad, Hasan Abid Urf Turabe Ali (Kansas State University, 2011)
NanoActiveTM metal oxide particles have the ability to destructively adsorb organophosphorus compounds and chlorocarbons. These nanomaterials with unique surface morphologies are subjected to separate, low concentrations of gaseous ammonia in air. NanoActiveTM materials based on magnesium oxide have large specific surface areas and defective sites that enhance surface reactivity and consequently improved adsorptivity. In gas contaminant removal by adsorption, presence of vast specific surface area is essential for effective gas-solid interaction to take place. This is also the case in many industrial and chemical applications such as purification of gases, separation and recovery of gases, catalysis etc,. Typically carbonaceous compounds are utilized and engineered in toxic gas control systems. The purpose of this study was to compare NanoActiveTM materials with carbon based compounds in the effectivity of toxic gas adsorption at low concentrations. A test facility was designed to investigate the adsorption properties of novel materials such as adorption capacity and adsorption rate. Adsorption capacity along with adsorption kinetics is a function of properties of the adsorbent and the adsorbate as well as experimental conditions. Nanomaterials were placed on a silica matrix and tested with increasing flow rates. Electrochemical sensing devices were placed at inlet and outlet of the facility to monitor real time continuous concentration profiles. Breakthrough curves were obtained from the packed bed column experiments and saturation limits of adsorbents were measured. Adsorption rates were obtained from the breakthrough curves using modified Wheeler-Jonas equation. The NanoActiveTM materials adsorbed ammonia though to a lesser extent than the Norit® compounds. This study also included measurement of pressure drop in packed beds. This information is useful in estimating energy losses in packed bed reactors. Brauner Emmet Teller tests were carried out for the calculation of surface area, pore volume and pore size of materials. These calculations suggest surface area alone had no notable influence on adsorption capacity and adsorption rates. This lead to the conclusion that adsorption was insignificant cause of absence of functional groups with affinity towards ammonia. In brief, adsorption of ammonia is possible on NanoActiveTM materials. However functional groups such as oxy-flouro compounds should be doped with novel materials to enhance the surface interactions.
Keywords: Nanoparticle; Adsorption of ammonia; Gas-solid phase interaction; Gas adsorption; Chemical Engineering (0542); Mechanical Engineering (0548); Nanoscience (0565)